Non-linear analysis of thin circular plates subjected to axisymmetric loads - Kadam, K. N.; Meghre, A. S. (Journal of Structural Engineering, 2025)
This paper presents geometric non-linear analysis of thin circular plates subjected to axisymmetric loads. The finite element method is used for the purpose. An annular circular ring type element is developed. It has two nodes (nodal lines) and each node is associated with three displacement parameters namely u,w and dw/dr . Essential details to calculate element tangent matrix of 6 × 6 size and element load vector are given. Two Gauss point integration is used to evaluate tangent stiffness matrix. Element load vector is derived using explicit integrations. Newton-Raphson method coupled with load stages is employed to solve non-linear equations. The proposed element has many advantages over triangular, rectangular, quadrilateral and curved quadrilateral elements, when used for analysis of circular plates. A computer program developed is used to analyse simply supported and clamped circular plates subjected to distributed loads and point load at the centre. The results are compared with the available solutions showing good agreement.